Intention to Screen for Cervical Cancer Among Child Bearing Age Women in Bahir Dar City, North-West Ethiopia: Using Theory of Planned Behavior - Alemnew W; Debalkie G; Azale T (Dove Medical Press, 2020)
Wallelign Alemnew, Getu Debalkie, Telake Azale Department of Health Education & Behavioral Sciences, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Wallelign Alemnew Tel +251 942 33 16 08Email wallelignaleminew@gmail.comBackground: Cervical cancer screening is consistently effective in reducing the incidence and mortality rates associated with cervical cancer. However, very few women have received cervical cancer screening in the developing countries including Ethiopia. Therefore, this study aims to assess cervical cancer screening intention and its predictors among child bearing age women in Bahir Dar city, North-West Ethiopia.Methods: A community-based cross-sectional study was conducted among 832 child bearing age women using a multistage sampling technique between March and April, 2018. Data were collected using a structured questionnaire through face-to-face interviews. Data were entered and analyzed using EpiData and SPSS version 20.0, respectively. Simple and multiple linear regression analyses were done to identify predictors of intention, and P< 0.05 was used as a cutoff to determine statistical significance at multiple regressions.Results: Eight hundred and thirty-two (98%) respondents participated in this study. The mean age of the participants was 31±SD 7.23 years, ranging from 18– 49 years. The majority (61.4%) of the participants were married. The mean score of intention to receive cervical cancer screening was 10.5± 2.03, with a minimum and maximum sore of 5 and 15, respectively. Four hundred and fifty-eight (55%) (95% CI=51.7– 58.3) respondents scored above the mean score. Direct perceived behavioral control (β=0.19, P< 0.001), direct subjective norm (β=0.06, P< 0.001), direct attitude (β=0.15, P< 0.001), and past screening experience (β=0.64, P< 0.001) were found to be significant predictors of intention.Conclusion: Perceived behavioral control, attitude towards the behavior, subjective norm, and past screening experience were the predictors of intention, and perceived behavioral control was the strongest predictor. Hence, behavioral change communication interventions are crucial to change their attitude and empower them to evaluate their control and normative beliefs.Keywords: cervical cancer, human papilloma virus, theory of planned behavior, Ethiopia